Treatment and molecular analysis of bullous pemphigoid with tofacitinib: a case report and review of current literature - Li, Xiang; Zhang, Lian; Gu, Hongzhi; He, Wanzhen; Zhai, Zhifang; Zhang, Mingwang (Frontiers in Immunology, 2024)
Background: Bullous pemphigoid (BP) is a rare, life-threatening autoimmune blistering disease with pruritus and tension blisters/bullous as the main clinical manifestations. Glucocorticosteroids are the main therapeutic agents for it, but their efficacy is poor in some patients. Tofacitinib, a small molecule agent that inhibits JAK1/3, has shown incredible efficacy in a wide range of autoimmune diseases and maybe a new valuable treatment option for refractory BP.Objective: To report a case of refractory BP successfully treated with tofacitinib, then explore the underlying mechanism behind the treatment, and finally review similarities to other cases reported in the literature.Methods: Case report and literature review of published cases of successful BP treatment with JAK inhibitors. The case report describes a 73-year-old male with refractory BP that was successfully managed with the combination therapy of tofacitinib and low-dose glucocorticoids for 28 weeks. Immunohistochemistry and RNA sequencing were performed to analyze the underlying mechanism of tofacitinib therapy. A systematic literature search was conducted to identify other cases of treatment with JAK inhibitors.Results: Throughout the 28-week treatment period, the patient experienced clinical, autoantibody and histologic resolution. Immunohistochemical analysis showed tofacitinib significantly decreased the pSTAT3 and pSTAT6 levels in the skin lesions of this patient. RNA sequencing and immunohistochemical testing of lesion samples from other BP patients identified activation of the JAK-STAT signaling pathway. Literature review revealed 17 previously reported cases of BP treated with four kinds of JAK inhibitors successfully, including tofacitinib (10), baricitinib (1), upadacitinib (3) and abrocitinib (3).Our findings support the potential of tofacitinib as a safe and effective treatment option for BP. Larger studies are underway to better understand this efficacy and safety.